2006
DOI: 10.1007/s11373-006-9115-5
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of LK-4, an analog of dextromethorphan on lipopolysaccharide-induced sepsis in rats

Abstract: SummaryDextromethorphan (DM), an anti-tussive agent, has been claimed to have anti-inflammatory and immunomodulatory effects in vitro. In our preliminary screening test, LK-4, an analog of DM, can afford more protection against circulatory failure induced by LPS than that of DM. Thus, the aim of this study was to evaluate the effects of LK-4 on sepsis induced by intravenous (i.v.) administration of lipopolysaccharide (LPS; 10 mg/kg) in anesthetized Wistar rats and survival rate by intraperitoneal administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…LK-4, an analog of DM, has greater potency of anticonvulsant/neuro-protective actions than DM has [16]. Jiau et al [17] found that treatment with LK-4 significantly attenuates the deleterious hemodynamic changes in rats treated with LPS. The induction of inducible NO synthase and the overproduction of NO and superoxide anions by LPS are also reduced by LK-4.…”
Section: Lk-4 An Analog Of Dextromethorphan Attenuates Lps-induced Smentioning
confidence: 99%
“…LK-4, an analog of DM, has greater potency of anticonvulsant/neuro-protective actions than DM has [16]. Jiau et al [17] found that treatment with LK-4 significantly attenuates the deleterious hemodynamic changes in rats treated with LPS. The induction of inducible NO synthase and the overproduction of NO and superoxide anions by LPS are also reduced by LK-4.…”
Section: Lk-4 An Analog Of Dextromethorphan Attenuates Lps-induced Smentioning
confidence: 99%
“…Therefore, we used two acute inflammation‐related cellular models: (1) activation of human neutrophils by receptor‐mediated (for example, N ‐formyl‐methionyl‐leucyl‐phenylalanine; fMLP) and non‐receptor‐mediated (for example, phorbol‐12‐myristate‐13‐acetate; PMA) induction of ROS production and Mac‐1 (CD11b/CD18) upregulation, and (2) LPS‐induced production of NO, ROS, and pro‐inflammatory cytokines, as well as iNOS expression and NF‐κB signalling in the murine microglial cell line, BV2, to evaluate the anti‐inflammatory effects of dimemorfan and the possible mechanisms of its actions in this study. Furthermore, LPS‐induced endotoxin shock in mice, a model of systemic inflammation ( Jiau et al ., 2006 ), was used to examine the in vivo activity of dimemorfan. Our results demonstrated that dimemorfan exhibits anti‐inflammatory properties through σ 1 ‐receptor independent mechanism(s) by inhibiting the production of NOX‐dependent ROS and iNOS‐dependent NO, as well as that of pro‐inflammatory cytokines, probably via modulation of NF‐κB signalling in activated inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we used two acute inflammation-related cellular models: (1) activation of human neutrophils by receptor-mediated (for example, N-formyl-methionyl-leucyl-phenylalanine; fMLP) and non-receptor-mediated (for example, phorbol-12myristate-13-acetate; PMA) induction of ROS production and Mac-1 (CD11b/CD18) upregulation, and (2) LPS-induced production of NO, ROS, and pro-inflammatory cytokines, as well as iNOS expression and NF-kB signalling in the murine microglial cell line, BV2, to evaluate the anti-inflammatory effects of dimemorfan and the possible mechanisms of its actions in this study. Furthermore, LPS-induced endotoxin shock in mice, a model of systemic inflammation (Jiau et al, 2006), was used to examine the in vivo activity of dimemorfan. Our results demonstrated that dimemorfan exhibits anti-inflammatory properties through s 1 -receptor independent mechanism(s) by inhibiting the production of NOXdependent ROS and iNOS-dependent NO, as well as that of pro-inflammatory cytokines, probably via modulation of NF-kB signalling in activated inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%